PERBEDAAN BENTUK LUKISAN SIDIK JARI, RIDGE COUNT, PALMAR PATTERN DAN SUDUT A-T-D ANTARA ORANG TUA ANAK SUMBING DENGAN ORANG TUA ANAK NORMAL DI TIMOR TENGAH SELATAN, NUSA TENGGARA TIMUR - Iriane, Vincentia Maria; Sanjoto, Pudjo; Loekito, Retno M. (Fakultas Kedokteran Universitas Brawijaya, 2003)
ABSTRACT The skin and lip-palate are formed nearly at the same period. They might be influenced by the similar genetic factor and environment.The objective of this research is to find the difference of dermatoglyphi between cleft-lip children’s parents and normal childern’sparents. The research is an analytical observation. It takes 50 samples of cleft-lip children’s parents and 50 samples of normalchildren’s parents. Each sample is classified into two groups, that is, (25) fathers and (25) mothers. Finger pattern, ridge count,palmar patern and a-t-d angle are dermatoglyphi variables to be measured. He result shows that: (1) The relationship betweenfather’s dermatoglifi and cleft-lip children is stronger than that between mother’s dermatoglifi and cleft-lif childern. (2) The percentageof whorl (W) pattern is higher in cleft-lip children’s parents; ehile the percentage of ulnar loop (UL)pattern is higher in normal children’sparents. (3) The ridge count of cleft-lip children’s fathers is normally higher than that of normal children’s fathers. (4) There is nodifference found in palmar pattern between cleft-lip children’parents and normal children’s parents. (5) A-t-d angle of the cleft lipschildren’s fathers is bigger than that of normal children’s fathers. (6) Cleft lips in South East Timor, East Nusa Tenggara is ancertrallyinherited. Key words: Dermatoglyphies, cleft lip patients parent